Fathers on Leave Alone: Does It Make a Difference to Their Lives? - Wall, Karin (2014)
Over the last two decades there has been a continuing enhancement of fathers’ leave entitlements. Depending on eligibility criteria and type of leave, fathers may be on leave at the same time as the mother or alone. Despite these developments, little is known about men on leave in a “home alone” manner. The experiences of fathers were explored through a qualitative study using a purposive sample of fourteen Portuguese fathers who took leave alone for one month. Lived experiences are diverse but emphasize the specific impact of leave alone and six key processes: negotiating, caregiving, learning, bonding, undoing gender and experiencing emotions. From a policy perspective, findings suggest that there are differences between family time and father’s time alone.